The F-Box Protein Fbp1 Regulates Virulence of Cryptococcus neoformans Through the Putative Zinc-Binding Protein Zbp1 - Han, Lian-Tao; Wu, Yu-Juan; Liu, Tong-Bao (Frontiers in Cellular and Infection Microbiology, 2021)
The ubiquitin-proteasome system (UPS) is the major protein turnover mechanism that plays an important role in regulating various cellular functions. F-box proteins are the key proteins of the UPS, responsible for the specific recognition and ubiquitination of downstream targets. Our previous studies showed that the F-box protein Fbp1 plays an essential role in the virulence of C. neoformans. However, the molecular mechanism of Fbp1 regulating the virulence of C. neoformans is still unclear. In this study, we analyzed the potential Fbp1 substrates using an iTRAQ-based proteomic approach and identified the Zinc-binding protein Zbp1 as a substrate of Fbp1. Protein interaction and stability assays showed that Zbp1 interacts with Fbp1 and is a downstream target of Fbp1. Ubiquitination analysis in vivo showed that the ubiquitination of Zbp1 is dependent on Fbp1 in C. neoformans. Subcellular localization analysis revealed that the Zbp1 protein was localized in the nucleus of C. neoformans cells. In addition, both deletion and overexpression of the ZBP1 gene led to the reduced capsule size, while overexpression has a more significant impact on capsule size reduction. Fungal virulence assay showed that although the zbp1Δ mutants are virulent, virulence was significantly attenuated in the ZBP1 overexpression strains. Fungal progression assay showed that the fungal burdens recovered from the mouse lungs decreased gradually after infection, while no yeast cells were recovered from the brains and spleens of the mice infected by ZBP1 overexpression strains. Thus, our results revealed a new determinant of fungal virulence involving the post-translational regulation of the Zinc-binding proteins.